COMMUNICATION WITH WHATSAPP: POLITENESS IN LANGUAGE OF STUDENTS OF THE POLIMARIN MARINE TRANSPORTATION STUDY PROGRAM IN THESIS PREPARATION - Alimatussa'diyah (UNIVERSITAS PGRI YOGYAKARTA, 2024)
The communication relationship between students and lecturers during the thesis writing guidance process is usually done via WhatsApp. Unfortunately, there are still some students who have not applied the principles of politeness so that the messages sent to the supervisor can potentially be impolite. This study aims to describe the politeness of the language of students of the Polimarin Marine Transportation Study Program to the supervisor in writing a thesis. The problem studied in this study is the compliance and violation of the principles of politeness of the language of students to the supervisor via WhatsApp messages. The method used in this study is a qualitative descriptive research method. The results of the study show that students comply with the principles of politeness more than they violate the principles of politeness. The compliance with politeness carried out by students is compliance with maxims of rather than feelings, maxims of generosity, maxims of agreement, and maxims of agreement with a total of 20 utterances. In pragmatics, proverbs can be interpreted as a type of speech that adheres to the principles of politeness. Furthermore, in violations of politeness, there are 15 student utterances that violate the principles of politeness. Based on these results, students actually already have an awareness of the importance of politeness when communicating.